WAYS TO OPTIMIZE THE TAX BURDEN ON ORGANIZATIONS IN THE REPUBLIC OF UZBEKISTAN - Yuldasheva Umida Asanaliyevna (American Journals, 2024)
In the conditions of market relations, the tax system is the basis of the financial and credit mechanism of state regulation of the economy. Taxes, like the entire tax system, are a powerful tool for managing the economy in market conditions. The effective functioning of the entire national economy depends on how well the taxation system is built. The state widely uses tax policy as a certain regulator of the impact on negative market phenomena in order to stabilize the economy and stimulate economic growth.
Keywords: Tax potential, tax administration, direct taxes, indirect taxes, tax efficiency, optimization of the tax burden.